MALAY ANNALS ON PERSIA: The Question of Royal Identity - Fuad Jabali (Sharia and Law Faculty, 2017)
This article tries to see the important points of reading Malay Annals which can be highlighted into two points: First, genealogically and the Second, the use of religion Abraham as a way to connect their kingdoms to global communities.